2021
DOI: 10.1371/journal.pone.0246001
|View full text |Cite
|
Sign up to set email alerts
|

Validation of dynamic virtual faces for facial affect recognition

Abstract: The ability to recognise facial emotions is essential for successful social interaction. The most common stimuli used when evaluating this ability are photographs. Although these stimuli have proved to be valid, they do not offer the level of realism that virtual humans have achieved. The objective of the present paper is the validation of a new set of dynamic virtual faces (DVFs) that mimic the six basic emotions plus the neutral expression. The faces are prepared to be observed with low and high dynamism, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…It is also true that some study found differences between young adults (20–39 years) and older adults (40–59 years) in favor of the younger group [ 36 ]. Therefore, and in line with a recent paper by the same authors validating the set of avatars in healthy population [ 24 ], three age groups were established for the analysis: 18–39 years, 40–59 years and above (here, 60–65 years old).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also true that some study found differences between young adults (20–39 years) and older adults (40–59 years) in favor of the younger group [ 36 ]. Therefore, and in line with a recent paper by the same authors validating the set of avatars in healthy population [ 24 ], three age groups were established for the analysis: 18–39 years, 40–59 years and above (here, 60–65 years old).…”
Section: Resultsmentioning
confidence: 99%
“…Some examples of DVFs are shown in Figure 1 . The complete description of the DVFs employed can be consulted in our previous experiment that validated the DVFs in 204 healthy people [ 24 ]. The software tool and the DVFs developed for this research are publicly accessible at Universidad de Castilla-La Mancha institutional repository RUIdeRA at , accessed on 20 April 2021.…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used an immersive version of the software originally designed for facial affect recognition under non-immersive virtual reality (García et al, 2020b;Fernández-Sotos et al, 2021). Therefore, the avatars used and the expressions they depict have already been validated by a sample of 204 healthy volunteers (50% women and 50% men) using a non-immersive display.…”
Section: Methodsmentioning
confidence: 99%
“…Very recently, our research team has carried out the validation of a set of dynamic avatars for the task of facial affect recognition (Fernández-Sotos et al, 2021). The validation was performed on a healthy population with the intention of being able to make a comparison in the near future with patients.…”
Section: Introductionmentioning
confidence: 99%